RATIO DECIDENDI IN DETERMINING RIGHTS TO RESTITUTION FOR CHILDREN AS VICTIMS OF RAPE - Jessyca Fatmawaty Hutagalung; Setiawan Noerdajasakti; Faizin Sulistio (CV. RADJA PUBLIKA, 2025)
This study discusses the legal regulations and basis for judges' considerations (ratio decidendi) in determining the right to restitution for children as victims of rape. The granting of restitution is often inconsistent due to differences in judges' interpretations of applicable legal norms, particularly the Child Protection Law and the Law on Sexual Violence. This study uses a normative juridical method with a qualitative approach through a review of the Cikarang District Court Decision Number 225/Pid.Sus/2024/PN.Ckr and the Padang District Court Decision Number 327/Pid.Sus/2019/PN.Pdg. The results of the study indicate that the judges in both decisions based their restitution determination on the principles of protecting victims' rights, restorative justice, and comprehensive recovery for the victims' physical, psychological, and social losses. In the Cikarang District Court Decision, restitution was awarded in the amount of Rp 29,800,000 and Rp 15,183,000 to the two child victims, while in the Padang District Court Decision the restitution awarded was much larger, namely Rp 194,125,000 to the victim's parents. The difference in nominal values occurred due to differences in the details of the proof of losses and the lack of standard technical guidelines in calculating restitution. From these findings, it can be concluded that although restitution has been recognized as an inherent right of child victims, the practice of determining restitution remains diverse and has the potential to create legal uncertainty. Therefore, clearer synchronization of regulations and technical guidelines is needed to optimize the fulfillment of restitution and ensure the protection and restoration of victims' human rights.